Réponses

2013-12-09T13:39:00+01:00
(3x-1)(5x+7)=0
tu as deux solutions :
1) 3x-1=0
   3x=1    x=1/3
2) 5x+7=0
   5x=-7      x=-7/5
(6x-12)(3x+9)=0
6x-12=0                   3x+9=0
6x=12                      3x=-9
x=2                          x=-3
(2x-8)(5x+3)
2x-8=0                     5x+3=0
2x=8                        5x=-3
x=4                           x=-3/5
(5-4x)(2x+7)=0
5-4x=0                     2x+7=0
-4x=-5                       2x=-7
x=5/4                          x=-7/2
(3a-5)²=0
3a-5=0
3a=5
a=5/3

36-9a²=0
(6-3a)(6+3a)=0
6-3a=0             6+3a=0
-3a=-6                3a=-6
a=2                   a=-2

4a²+4a+1
(2a+1)²
2a+1=0
2a=-1
a=-1/2

9a²-12a+4=0
(3a-2)²=0
3a-2=0
3a=2
a=2/3